Prevalence and determinants of undernutrition in the urban slums of Belagavi: a cross-sectional study among young children - Oswal, Deshna; Angolkar, Mubashir; Mahantashetti, N. S.; Singh, Mayank; Haritay, Shivani; Godbole, Madan (Frontiers in Pediatrics, 2025)
IntroductionRapid urbanization in low- and middle-income countries has led to the expansion of slums, where children face a heightened risk of undernutrition. This study aimed to determine the prevalence of undernutrition and its determinants among children residing in the urban slums of Belagavi, Karnataka.MethodsThe anthropometric measurements, clinical signs, demographic information, and dietary history of children aged 9–36 months from urban slums were assessed. The chi-square test, bivariate analysis, and multivariable logistic regression were used to identify the risk factors at the child, maternal, and household levels for undernutrition.ResultsThe prevalence of stunting, wasting, and underweight among children aged 9–36 months was 44%, 11%, and 25%, respectively. Common predictors of stunting and underweight included low birth weight, short maternal stature, lack of maternal exposure to print media, and maternal consumption of iron–folic acid during pregnancy. A lack of maternal exposure to print media was also associated with wasting. In addition, stunting was linked to male sex and low maternal education, while underweight was associated with children from non-Hindu and non-Muslim religious backgrounds, and maternal lack of autonomy or control over household finances. Wasting, however, was associated with the 24–36 months age group and maternal gestational diabetes.ConclusionA high level of undernutrition was observed in the urban slums of Belagavi, with the prevalence of stunting exceeding the national and state averages. Undernutrition was linked to maternal, child, and household factors, including low birth weight, maternal stature, education, and autonomy.